Asparagus officinalis polysaccharide-loaded liposomal gels alleviate skin inflammation via inhibiting the NF-κB/MAPK pathways - Rongrui Zhang; Yu Xiong; Yujin Ma; Yafei Ma; Nuo Li; Yan Ren; Lili He; Lu Han; Jun Ni; Zhi-xiang Yuan (Journal of Functional Foods)
Asparagus officinalis L. has long been used as a medicinal food since ancient times. Despite identifying the active compounds, the anti-inflammatory properties of these compounds remain underexplored. This study explored the anti-inflammatory activity of white asparagus polysaccharide (WAPS) against skin inflammation. WAPS, a pectin polysaccharide, was identified to coexist with α-glycosidic and β-glycosidic linkages glucan and probably has triple-helix confirmation suggested by Fourier-transform infrared and nuclear magnetic resonance spectroscopy. Cellular experiments indicated that WAPS attenuated the expression of inflammatory cytokines and enhanced macrophage viability. Skin inflammation was ameliorated with WAPS liposomal-loaded gel; the mechanism regulating NF-κB/MAPK signal pathways was further explored. Notably, the formulation augmented the bioavailability of WAPS, downregulated the expression of NF-κB p50 and MMP9, and amplified the inhibitory potential of WAPS against inflammation. This study suggests WAPS as a medicinal substance with anti-inflammatory efficacy.